Foreign Experience In Managing the Quality of Labor Resources - Rasulov Shavkat Sharof uglu, (Journal of Artificial Intelligence and Digital Economy, 2024)
In this article, foreign experience in managing the quality of labor resources and proposals and recommendations for improving the efficiency of the regional labor market have been developed.